Corpomídia e gênero: comunicação na prática instável da existência - Carletti, Isabela (2019)
The use of technologies has been producing new cognitive habits. Social media make the engagement easier for those who wasn’t used to speak before, more recently, it has become an arena for the proliferation of hate speech, intolerance and violence against groups called minority groups. Within the capitalist context that governs us, much has been published about gender, sexuality and LGBT movement. It is in this complex universe that matters about transgender people become the subject of this dissertation. Observes the emergence of biopower (1988, Foucault), which gives birth to a new form of governability of bodies. It is extremely important to evidentiate macro-and micro-power structures of life management, presents in public or private institutions, in the discourses of medicine, church and civil society, among others. Within this subject, the dissertation has as object of investigation the work we realized together with transgender people at the popular education called “TransFormação”. The scope is to discuss and problematize in the matter of sexuality, gender and about the transition processes, what happens when one begins to understand that we are media of ourselves (2005, Katz and Greiner) and also the need to overturn and propose new unstable paradigms for the existence of all. The issues/problem of which part is to understand how the power devices operate in the processes of transitions of the transgender people. And the hypothesis that was born was that a dance work can destabilize places of certainties and construct ways of encounter with ourselves that strengthen us and stimulate us to seek a space of conviviality in society. The theoretical basis will be based on the Bodymedia Theory (2005, Greiner and Katz) and the formulations of Frost (2016) to read the relations between body and environment; Preciado (2008; 2017) will bring contributions to the understanding of the bodies in the contemporary pharmacopornographic and propositions for a contrassexual practice; Butler (2012) will point issues pertaining to gender performativity. In order to propose the dissolution of the current thinking, which governs the practices related to discourses on gender and sexuality, the methodology will be that of the bibliographical revision, dedicated to recognizing the ways of control to which we are submitted, plus the practical experience of the classes at the popular course, in which emerged ways of destabilizing the paradigms imposed and build new ways of coping the situations of violence that affect this group of people, Santos (2010) and Brandão (1985) are part of the construction of thought that gave rise to these practices. The Coletivo Brada will also be presented. The ways of creation and discourses produced by this group when constructing a dance work point out that it is more than ever necessary to affirm that the consciousness of the movement is self-consciousness and that acting towards that knowledge is a political act